The Relationship between Religious Symbols and Intergroup Attitudes among Majority Group Members - Shamoa-Nir, Lipaz; Razpurker-Apfeld, Irene (International Journal of Psychosocial Rehabilitation, 2019)
Precursors of intergroup tension have been researched in divided societies in an aim to understand social problems. It seems that negative attitudes towards the out-group stem from a combination of two contrasting processes, in-group preference and out-group derogation. As research has progressed, a growing interest has been shown in understanding the emergence of negative out-group attitudes while focusing on variables such as intergroup threat, contact between groups, social norms and religion. This study investigated whether priming of religious concepts influences prejudices and threat perceptions of Jewish majority members towards Arab minority members in Israel. We attempted to find priming effects of religious content on prejudice and perceived threat with religiosity as a moderating variable. Religious words were primed via search puzzles, and were then followed by questionnaire filling. Priming effects were not found for prejudice or threat perceptions, probably due to social desirability effects. Although this is a preliminary investigation, this paper highlights the importance of studying the contribution of religious content to intergroup attitude formation for majority group members toward minority members.